1996
DOI: 10.1016/0735-1097(95)00510-2
|View full text |Cite
|
Sign up to set email alerts
|

Triggers of myocardial ischemia during daily life in patients with coronary artery disease: Physical and mental activities, anger and smoking

Abstract: Triggers of ischemia in patients with coronary artery disease during daily life include not only strenuous exercise, but also activities involving low levels of exertion, such as anger and smoking. Mental activities appear to be as potent as physical activities in triggering daily life ischemia. Coffee and alcohol consumption are related to ischemia only by virtue of their associations with smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
8

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(85 citation statements)
references
References 37 publications
1
76
0
8
Order By: Relevance
“…While mental-stress induced ischemia can be observed reliably in the laboratory among CAD patients (e.g., Rozanski et al, 1988), it has also been observed during daily life activities using ambulatory monitoring devices and structured diaries (e.g., Gabbay et al, 1996;Gullette et al, 1997). These approaches thus help researchers observe the behaviors or specific stressful events which trigger ischemic episodes, and by extension, other cardiac events (Kop, 1999).…”
Section: Acute Stress and Ischemiamentioning
confidence: 99%
See 3 more Smart Citations
“…While mental-stress induced ischemia can be observed reliably in the laboratory among CAD patients (e.g., Rozanski et al, 1988), it has also been observed during daily life activities using ambulatory monitoring devices and structured diaries (e.g., Gabbay et al, 1996;Gullette et al, 1997). These approaches thus help researchers observe the behaviors or specific stressful events which trigger ischemic episodes, and by extension, other cardiac events (Kop, 1999).…”
Section: Acute Stress and Ischemiamentioning
confidence: 99%
“…Electrocardiographic measures have been used in the laboratory and in ambulatory Holter monitoring to document how acute stress may elicit ischemia (Schiffer, Hartley, Schulman, & Abelmann, 1976;Gabbay et al, 1996).…”
Section: Ischemia Assessed Via Electrocardiographymentioning
confidence: 99%
See 2 more Smart Citations
“…2, 3 Several studies have shown that the development of myocardial ischemia in this setting, predicts ischemia during daily life, is a poor prognostic factor and is linked to fatal and nonfatal cardiac events in patients with CAD. [2][3][4][5][6][7][8] Exercise or adenosine stress testing is commonly used in clinical settings as a risk stratification tool in patients with CAD. However there is evidence that these testing modalities may not adequately assess the likelihood of risk related to mental stress.…”
Section: Introductionmentioning
confidence: 99%